A study of conditioned inhibition procedures in relation to individual differences and disorder - He, Zhimin (2011)
Classical conditioning and conditioned inhibition are fundamental for cognitive processes in both animals and humans. Conditioned inhibition is involved in a wide range of normal behaviour – and its disruption could produce a wide range of behavioural deficits. For example, lack of inhibitory control has been argued to lie at the core of impulsivity (Buss & Plomin, 1975). Impulsivity is one of the core features in some of the clinical groups, such as schizophrenic patients and patients with cluster B personality disorders (PD), especially patients with PD within forensic populations (Hare et al., 1991; Munro et al., 2007). Previous research studied impulsivity by using some laboratory behaviour learning tasks (e.g. Go-NoGo tasks). People with higher impulsivity have difficulty withholding responding which is demonstrated by poor performances in these tasks. Such tasks measured participants’ ability to inhibit pre-potent motor responses, and these tasks are usually thought to involve inhibition of stimulus-response (S-R) association. To date, little research has explored the inhibition of stimulus-stimulus (S-S) associations (formally ‘conditioned inhibition’, CI) in relation to individual differences, and no research has explicitly examined CI learning in any clinical groups.